Mutations in TP53 or DNA damage repair genes define poor prognostic subgroups in primary prostate cancer - Nientiedt, Cathleen; Budczies, Jan; Endris, Volker; Kirchner, Martina; Schwab, Constantin; Jurcic, Christina; Behnisch, Rouven; Hoveida, Shirin; Lantwin, Philippa; Kaczorowski, Adam; Geisler, Christine; Dieffenbacher, Svenja; et al. (Urologic oncology, 2022)
Background - Mutations in DNA damage repair genes, in particular genes involved in homology-directed repair, define a subgroup of men with prostate cancer with a more unfavorable prognosis but a therapeutic vulnerability to PARP inhibition. In current practice, mutational testing of prostate cancer patients is commonly done late i.e., when the tumor is castration resistant. In addition, most sequencing panels do not include TP53, one of the most crucial tumor suppressor genes in human cancer. In this proof-of-concept study, we sought to extend the clinical use of these molecular markers by exploring the early prognostic impact of mutations in TP53 and DNA damage repair genes in men with primary, nonmetastatic prostate cancer undergoing radical prostatectomy (RPX).